PENGARUH LEADER MEMBER EXCHANGE TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL INTERVENING - Rahayu Setyati; Woro Utari (Journal of Applied Management and Accounting Science, 2023)
This study aims to describe LMX, Employee Engagement and OCB at the Department of Industry and Manpower, Bojonegoro Regency. To examine and analyze the effect of LMX on Employee Engagement, the effect of Employee Engagement on OCB, the effect of LMX on OCB, and the effect of LMX on OCB through Employee Engagement at the Department of Industry and Manpower, Bojonegoro Regency. This type of research is explanatory with a quantitative approach. The population is all employees of the Department of Industry and Manpower of Bojonegoro Regency, amounting to 55 people. The sample was determined as many as 55 people with census sampling technique. To perform data analysis using path analysis with Partial Least Square (PLS). Based on the results of the analysis, it can be concluded that LMX has a significant effect on Employee Engagement at the Department of Industry and Manpower, Bojonegoro Regency. Employee Engagement has no significant effect on OCB at the Department of Industry and Manpower, Bojonegoro Regency. LMX has a significant effect on OCB in the Department of Industry and Manpower, Bojonegoro Regency. LMX has a significant effect on OCB through Employee Engagement at the Department of Industry and Manpower, Bojonegoro Regency.